PWE-171 Mobile element insertions are frequent and potentially mutagenic events in oesophageal carcinogenesis. (22nd June 2015) - Paterson, AL; Weaver, JMJ; Eldridge, M; Tavare, S; Fitzgerald, RC; Edwards, PAW
Abstract : Introduction: Mobile elements (ME) are repeat sequences found throughout the genome that can move to, or insert copies of themselves at, other genomic loci. The most active generate new copies by retrotransposition: mRNA is transcribed then cDNA is synthesised by reverse transcription and inserted. Such events may also transduce small fragments of unique DNA sequence found adjacent to the ME, thus making them identifiable in sequencing data. ME retrotransposition has recently been described in several tumour types, but how frequent and widespread this is, and whether it contributes significantly to gene mutation, is not yet clear. This project aimed to explore whether ME retrotransposition was identifiable in oesophageal adenocarcinomas (OACs) and its mutagenic potential. Method: Possible ME insertions were identified from whole genome sequencing data for 43 OACs by three methods. The first identified cases where the same short unique sequence from one chromosome, which would be a sequence transduced by a mobile element, was joined to multiple different loci within the same tumour. The second method isolated rearrangements adjacent to 90 retrotransposition-capable MEs. The third identified all poly (A) sequences >20 nucleotides long that appeared to be unique to the tumour. A subset of 71 potential insertions was tested by PCR using patient-matched normal DNA as a control. Results: The first two approaches combined identified 649 candidate ME retrotransposition events. 42/45 (93%) inserts selected for PCR verification had tumour-unique products, with sequencing demonstrating target site duplication, a poly (A) tract and ME repeat sequence and/or unique transduced sequence, confirming these to be retrotransposition events. 40/43 (93%) tumours had at least one probable ME insertion with a mean of 15 per tumour (range 0–153). 193/649 (30%) inserts fell within genes, mainly intronic, however five were within exons. These two approaches identified retrotransposition events that transduced unique sequence downstream of MEs; however this is only a subset of ME insertions. A search for poly (A) tracts, a marker of all ME insertions, in tumour-unique loci was undertaken to estimate their overall frequency. In total, 5422 tumour-unique poly (A) tracts were identified in the 43 OACs, mean 126 (range 6–858) per tumour. 24/26 (92%) randomly selected inserts had a tumour-specific product on PCR validation. Conclusion: ME retrotransposition is highly prevalent in OACs, and occurs frequently in each tumour. Since almost all ME insertions are capable of interrupting mRNA transcription, they could contribute substantially to gene mutation. Disclosure of interest: None Declared.